The The Influence of Social Media on Students’ Vocabulary Mastery - Maria Kristin Silaen; Sanggam Siahaan (The Future of Education Journal, 2026)
Social media has become an important learning resource that supports English language learning, particularly vocabulary mastery. However, previous studies have mainly focused on specific social media platforms or students’ perceptions, resulting in limited comprehensive understanding of the overall influence of social media on English vocabulary learning. Therefore, this study aimed to investigate the influence of social media on students’ English vocabulary mastery through a library research approach. This study employed a library research design by reviewing 22 relevant studies published between 2020 and 2026. The data were collected from journal articles accessed through Google Scholar and other academic databases. The selected studies were analyzed using qualitative content analysis by identifying recurring themes and synthesizing the findings. The results revealed that social media contributes positively to students’ English vocabulary mastery. Five major findings were identified. First, social media facilitates vocabulary acquisition by exposing students to authentic English-language content. Second, it improves students’ vocabulary mastery through engaging and contextualized learning experiences. Third, social media promotes autonomous vocabulary learning by encouraging self-directed learning strategies. Fourth, it increases students’ motivation and interest in learning English vocabulary through interactive and enjoyable content. Nevertheless, several challenges were identified, including distractions, exposure to informal language, misinformation, and concerns regarding content reliability. In conclusion, social media can serve as an effective supplementary learning tool for enhancing students’ English vocabulary mastery when used purposefully and critically.